The Effect of “Eclice” an Educational Media on Science Literacy among 5-6 Year-Old Children in Sado, Thailand - Handriani, Syafira; Adhe, Kartika Rinakit; Ningrum, Mallevi Agustin; Safitri, Dhian Gowinda Luh (Jurnal Pendidikan Anak, 2025)
Climate change is a global issue that is imperative to introduce to children from an early age so that they develop adequate science literacy to understand and respond to its impact. This study aimed to develop eclice media as an e-book on climate change to enhance the science literacy of children aged five to six. The research method employed the pre-experimental design one group pretest and post-test, with the subject being 20 children aged 5-6 years at Sadao Kindergarten Thailand. The instruments utilized included questionnaires, observations, and science literacy tests. The effectiveness of the media was determined by analysing the data using the Wilcoxon test. The findings indicated that the use of eclice media was both practical (100% feasibility) and led to a substantial enhancement in children’s science literacy (p < 0.05). The research findings suggest that eclice can serve as an alternative to innovative learning media, aiming to foster science literacy from an early age and enhance the role of teachers and parents in environmental education.